Challenges and Visions for Infectious Diseases in Colombia during the COVID-19 Peripandemic Transition 2021-2023 - Alfonso J. Rodriguez-Morales (Asociación Colombiana de Infectología, 2021)
After the first 20 months of the Coronavirus Disease 2019 (CO-VID-19) pandemic, caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), many lessons have been learnt in Colombia, Latin America and the world from many points of view1. When the COVID-19 arrived to Colom-bia,2 and other countries in the region3, many other infectious diseases concerned affected us, including previous epidemics of chikungunya4,5,Zika6,7,and most recently of dengue8, as well as, the impact of certain vaccine-preventable diseases, such as measles, particularly linked to the forced migration from Ve-nezuela, and the persistent threat of malaria and other vector-borne diseases, HIV and tuberculosis, among many other9-11. Even more, in Colombia, as well as in other countries of Latin America, a envisioned challenge in pediatrics is to recover the appropriate vaccination coverage for other diseases different to COVID-19, that have decreased during the pandemic12.